2016
DOI: 10.1088/0953-8984/28/39/395401
|View full text |Cite
|
Sign up to set email alerts
|

The structures of interstitial hydrogen centers in VO2in the dilute limit from their vibrational properties and theory

Abstract: The introduction of a large concentration of H into VO2 is known to suppress the insulating phase of the metal-insulator transition that occurs upon cooling below 340 K. We have used infrared spectroscopy and complementary theory to study the properties of interstitial H and D in VO2 in the dilute limit to determine the vibrational frequencies, thermal stabilities, and equilibrium positions of isolated interstitial H and D centers. The vibrational lines of several OH and OD centers were observed to have therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…It is reported that hydrogen incorporated into M-VO 2 crystals can stabilize the metallic VO 2 phase at room temperature [10][11][12][13][14] and further lead to an insulating phase in the high doping regime [15]. Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is reported that hydrogen incorporated into M-VO 2 crystals can stabilize the metallic VO 2 phase at room temperature [10][11][12][13][14] and further lead to an insulating phase in the high doping regime [15]. Fig.…”
mentioning
confidence: 98%
“…It is reported that hydrogen incorporated into M-VO 2 crystals can stabilize the metallic VO 2 phase at room temperature [10][11][12][13][14] and further lead to an insulating phase in the high doping regime [15]. Explained in the context of crystal-field theory [16,17], the H-doping induced band structure evolutions is represented in Fig.…”
mentioning
confidence: 99%